Migrasi Autentikasi dari Pam ke LDAP di Universitas Kristen Petra - Julio Christian Salim; Justinus Andjarwirawan; Henry Novianus Palit (Jurnal Infra, 2016)
Authentication at Petra Christian University using an account that is stored in the local user operating system on the server John and Peter. Puskom need to store more data than it currently can. Therefore, LDAP is used to replace the local user account on the storage operating system. Existing application uses PAM through dovecot / POP3 to authenticate.Work on the thesis focuses on the implementation of LDAP at Petra Christian University and migration of accounts and applications. Implementation and migration using account data that is stored on a server John and Peter. Applications are made for searching and modify existing account or create new account. Applications are made to support the needs Puskom.Based on testing performed, the account migration is successful. Testing the migrated account was performed using multiple accounts belongs to students and lecturer. Also response time that is needed by LDAP to authentication request is shorter than autentication using existing system which use POP3.